KONDISI UDARA AMBIEN DAN TINGKAT KEBISINGAN DI KAWASAN PELABUHAN PERIKANAN SAMUDERA BITUNG - Passion Christian Zebblon (Sam Ratulangi University, 2021)
This study aims to determine the operational impact Bitung Fishing Port (BFP) on ambient air conditions and noise level in the fishing port area.Â This study was conducted at the BFP and started from November 1, 2020 â€“ February 5, 2021. BFP is located in Aertembaga Satu Village, Aertembaga District, Bitung City, North Sulawesi Province. This study is a type of quantitative research carried out by survey methods and analysis of research results is carried out descriptively. Primary data comes from the results of direct measurements in the field (4 sampling points) on November 2, 2020. The data was analyzed at the Manado Industrial Research and Standardization Center on November 3, 2020. The results of the analysis were sent to PPS Bitung on January 10, 2021. Secondary data is sourced from time series data on ambient air and noise measurements from the BFP RKL-RPL report from 2014 to 2019. The measurement period for ambient air (SO2, NO2, CO, TSP) and noise levels is carried out 2 times a year. Based on the study results, it can be seen that the status of environmental management and itâ€™s application is still quite good, as evidenced by the conditions of contamination in ambient air and the level of air noise in the fishing port area is still below the quality standard.